A STUDY ON STUDENTS’ INTRINSIC MOTIVATION IN ONLINE LEARNING ENGLISH USING SHORT VIDEO OF INSTAGRAM REELS AS A MEDIA - Waode Hamsia (STKIP PGRI Jombang, 2022)
This research was design in descriptive qualitative research to find the students’ motivation in online learning English. The data was collected and analyzed from several related of literature on the application of videos in the short videos of Instagram Reels. This research aimed that the video Reels as media can make students more enjoyed process teaching and learning. It seems using videos can give a relaxing situation for students in learning English. It also can make students more active and easy to understand the material since the video contains pictures and audio that causes students to see the material directly. The subjects were the second semester of students in Intensive English Course as the EFL Classroom. The teaching and learning activities in the class which are seems divided into three steps, e.g., Pre-activity, main activity, and activity of the last post. The analysis recommends the lecturer, as a model should have planning systematically what Lecturer should do during teaching and learning process to deliver good material in online class.